Compliance and adherence to drug treatment on patients with chronic kidney disease in high prevalence areas of North Central Province, Sri Lanka - Chathuranga, Dilan; Manathunga, Harith S.; Gunasekara, Sumali K.; Jayasekara, Kithsiri B.; Sanjeewani, Ashoka (International Journal Of Community Medicine And Public Health, 2021)
Background: Chronic kidney disease that cannot be explained by traditional factors such as hypertension, diabetes mellitus is called chronic kidney disease unexplained etiology. With limited evidence on the success of interventions in enhancing medication adherence, this study was designed to test patient compliance and adherence on taking medication in North Central Province in Sri Lanka. Methods: A cross sectional study was conducted in a selected area of NCP to identify compliance, adherence. Data was collected using an interviewer administered questionnaire by visiting patients at their own residences. Results: A total of 200 people participated in this study. 92.5% of the population was involved in agriculture and 63% worked more than 1 acre of farmland. Among the selected population (74%) were not educated about the side effects of medication. 60.5% had missed taking their medicines during the prescribed time period. The entire population of the study was selected among patients having a monthly income of less than 15,000 Sri Lankan rupees. There was a statistically significant association in missing doses with land extent, patient’s income and stages of the disease. Conclusions: Non adherence and compliance to the medication is common in patients that worked in largely extended lands, were in late stages of the disease and had reduced income. Compliance and Adherence to the medication can be enhanced by proper counseling and improving patient’s knowledge about their medication.